2012
DOI: 10.1002/anie.201205905
|View full text |Cite
|
Sign up to set email alerts
|

Changing the Enzyme Reaction Rate in Magnetic Nanosuspensions by a Non‐Heating Magnetic Field

Abstract: Desaktiviert und deformiert werden Enzyme, die auf magnetischen Nanopartikeln (MNPs) immobilisiert sind, beim Anlegen von magnetischen Feldern. Diese Veränderungen resultieren aus der erneuten Ausrichtung der MNPs im AC-Magnetfeld, die mit den MNP verknüpfte Polymerketten unter Belastung setzt. Für immobilisierte Enzymmoleküle auf einem MNP-Aggregat ergeben sich dadurch Deformationen und irreversible (oder lange anhaltende) Konformationsän-derungen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 25 publications
0
39
1
Order By: Relevance
“…Thus, a theoretical study by Rabin has concluded that conditions of hyperthermia could only be met within a cluster of several cells that are densely and fully loaded with MNPs [77]. Similar considerations and conclusions based on the theoretical analysis of the thermal diffusion using the Fourier differential heat equation were presented in a number of other studies [33,7882]. Such analysis is presented in Supplementary material 2.…”
Section: Rf Magnetic Hyperthermiamentioning
confidence: 55%
See 2 more Smart Citations
“…Thus, a theoretical study by Rabin has concluded that conditions of hyperthermia could only be met within a cluster of several cells that are densely and fully loaded with MNPs [77]. Similar considerations and conclusions based on the theoretical analysis of the thermal diffusion using the Fourier differential heat equation were presented in a number of other studies [33,7882]. Such analysis is presented in Supplementary material 2.…”
Section: Rf Magnetic Hyperthermiamentioning
confidence: 55%
“…Our studies have shown the possibility of a magneto-mechanical change of protein (enzyme) conformation and altering the rate of the biocatalytical reaction by an AMF in the absence of heating [33,132]. The effects of mechanical deformation on the functional properties of proteins and other bioactive molecules immobilized on polymeric supports have been studied for nearly 40 years [133,134].…”
Section: Observation Of Magneto-mechanical Actuation In Biologicalmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation suggests the significance of magneto-mechanochemical effects induced by the realignment of MNP magnetic moments in an alternating current magnetic field rather than traditional heating. [28] In this article, we discuss the work on the synthesis and characterization of Fe 3 O 4 @Au nanoparticles for a biomedical application that has occurred since 2006. We exclude the methods of synthesis of dumbbell, cluster/shell nanoparticles and iron oxide MNPs with Au seeds on the surface; other methods are described in other excellent reviews.…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, it could be induced by local dissipation of heat (local heating) in the vicinity of the SPION surface, which results in protein denaturing and disruption cell membranes, especially in the case of the EGF-targeted nanoparticles. On the other hand, some authors suggested that there could be induced mechanical effect due to realignment of the magnetic nanoparticles along the field, which can disrupt or denature proteins and structures joining the nanoparticles and thereby affect the cell signaling [232, 233]. …”
Section: Nanomedicine-based Therapies Against Cscsmentioning
confidence: 99%